PENGENALAN DAN PRAKTIK MANAJEMEN DAN PENCATATAN KEUANGAN KELUARGA BAGI IBU RUMAH TANGGA PEGIAT UMKM - Liana Dewi; Revalina Yunijar; Via Fitriani (Jurnal Bakti kepada Masyarakat, 2025)
As the smallest social organization, the family can make a significant contribution to the progress of a nation. A healthy family economy will positively impact the national economy. However, unfortunately, there are still problems encountered in family financial management originating from internal and external factors, including minimal financial literacy, difficulty determining priorities in family finances, and even termination of employment. Housewives play a crucial role in family financial management. To ensure successful family financial management, many housewives choose to carry out dual roles in managing family finances while also being MSME activists. Linggajaya Village, Mangkubumi District, Tasikmalaya City, is one of the areas with many PKK programs aimed at improving the quality of family management for its community. Housewives who are also MSME activists in the Linggajaya Village area need to be educated on the importance of family financial management using technical accounting approaches and religious morality. The implementation of the activity consisted of educational activities in the form of management workshops and financial recording for housewives who are MSME activists, accompanied by an understanding of the Islamic perspective on family financial management. After the activity, participants filled out an activity evaluation form as input for the organizers. Participants are able to understand the concepts and practices of family and business financial management from a religious and accounting perspective and intend to apply them independently.